Efficacy of LED Photobiomodulation for Functional and Axonal Regeneration After Facial Nerve Section-Suture - Er-Rouassi, Hafsa; Benichou, Luc; Lyoussi, Badiaa; Vidal, Catherine (Frontiers in Neurology, 2022)
Facial nerve damage can lead to partial or total facial nerve palsy. Photobiomodulation has been reported to improve and accelerate functional recovery following peripheral nerve lesion, depending on the type of lesion and the light exposure parameters used. The aim of this study was to investigate the effects of infrared exposure on functional and axonal regeneration after section-suture of the distal branches of the facial nerve: the buccal and marginal mandibular branches and the distal pes. The animals underwent surgery and were irradiated with infrared light at 850 nm twice daily from day 1 to day 16. The recovery of facial function was then studied at both the behavioral and morphological levels. Behavioral analyses were performed by videoscoring with a high-speed camera and using various devices to assess the recovery of whisker movement on the lesioned side from day 1 to day 30. We also assessed nasal deviation toward the intact side and the ability to close the ipsilateral eyelid completely from day 1 to day 38 and from day 1 to day 50, respectively. For morphological analyses, we assessed the re-establishment of facial motoneuron labeling with Fluorogold®, an immunofluorescent retrograde marker of axonal transport injected into the vibrissae, on D10, D14 and D30. We found that whisker movements recovery was significantly faster in treated than in control mice. A complete disappearance of nasal deviation was observed at 2 weeks in infrared-treated lesioned mice and at 5 weeks in controls. Complete eyelid closure was observed 3 weeks after surgery in treated animals and 6 weeks after surgery in controls. Finally, normal fluorogold labeling of the facial nuclei complex was restored 30 days after surgery in the treated animals, but no such restoration was ever observed in control animals. In conclusion, our data show that IR treatment at a distal site has a significant positive effect on facial nerve recovery. These findings pave the way for the clinical use of infrared photobiomodulation in patients with nerve lesions.